FORMATION OF CREATIVE ACTIVITY OF STUDENTS BASED ON STEAM APPROACH IN TEACHING CHEMISTRY - F.A., , Alimova; H., , Askaralieva (Journal of Learning on History and Social Sciences, 2024)
This article discusses the methodology for organizing classes based on the STEAM approach to teaching chemistry. STEAM learning is an innovative methodology that represents a full-fledged systematic education, including the study of natural sciences together with engineering, technology, art and mathematics. Based on this technology, it is also possible to realize the creative ideas of students in educational institutions when studying the basics of chemistry.